Exploring Factors of Absenteeism Among Students Attending Community Medicine Department - Joshi, Harshdeep; Monga, Shamim; Raina, Sunil (Indian Journal of Community Health, 2022)
Context: Frequent absence from classes may lead to improper learning and poor academic performance. Absenteeism can make teaching - learning environment unwelcoming and impacting those also who attend classes regularly. Aims & Objectives: To explore factors responsible for absenteeism among second professional students attending Community Medicine Department and to formulate recommendations to deal with absenteeism. Material and Methods : A Cross sectional study was conducted among 132 second professional medical undergraduate students attending Community Medicine Department in a teaching hospital. A self-designed pre validated questionnaire comprising of various sections related to teaching –learning factors was used to explore factors responsible for student absenteeism. Faculty perception regarding student absenteeism and recommendations formulated to deal with it were recorded separately. Data analysis: Data was entered in MS Excel and Chi Square test was used for analysis. Results: Among 132 study participants, majority of the participants (62.1%) were females who were residing in hostels. Highest percentage of absenteeism (40.1%) was during examination time. Extracurricular activities like sports/gym, browsing net and parties were significantly (p<0.001) associated with absenteeism. Conclusions: Absenteeism can adversely affect academic performance and low attendance can demotivate teachers also to teach with keen interest.